Impact of specimen adequacy on the assessment of renal allograft biopsy specimens - Cimen,S. (2016)
The Banff classification was introduced to achieve uniformity in the assessment of renal allograft biopsies. The primary aim of this study was to evaluate the impact of specimen adequacy on the Banff classification. All renal allograft biopsies obtained between July 2010 and June 2012 for suspicion of acute rejection were included. Pre-biopsy clinical data on suspected diagnosis and time from renal transplantation were provided to a nephropathologist who was blinded to the original pathological report. Second pathological readings were compared with the original to assess agreement stratified by specimen adequacy. Cohen's kappa test and Fisher's exact test were used for statistical analyses. Forty-nine specimens were reviewed. Among these specimens, 81.6% were classified as adequate, 6.12% as minimal, and 12.24% as unsatisfactory. The agreement analysis among the first and second readings revealed a kappa value of 0.97. Full agreement between readings was found in 75% of the adequate specimens, 66.7 and 50% for minimal and unsatisfactory specimens, respectively. There was no agreement between readings in 5% of the adequate specimens and 16.7% of the unsatisfactory specimens. For the entire sample full agreement was found in 71.4%, partial agreement in 20.4% and no agreement in 8.2% of the specimens. Statistical analysis using Fisher's exact test yielded a P value above 0.25 showing that - probably due to small sample size - the results were not statistically significant. Specimen adequacy may be a determinant of a diagnostic agreement in renal allograft specimen assessment. While additional studies including larger case numbers are required to further delineate the impact of specimen adequacy on the reliability of histopathological assessments, specimen quality must be considered during clinical decision making while dealing with biopsy reports based on minimal or unsatisfactory specimens.